The Oxford treasury of world stories - Christopher, Michael; Stuart-Clark, Harrison (New York : Oxford University Press, 1998)
Presents a collection of stories from around the world. This book features funny stories and clever stories, sad stories and strange stories, each one reflecting the country from which it comes. It begins with Anansi the spider, tricking his friends and winning, as usual; and ends with a woodcutter being lured away and lost forever in a jungle.
Keywords: Children's stories, English; Folklore; Short stories